Generalised density function estimation using moments and the characteristic function - Esterhuizen, Gerhard (Stellenbosch : University of Stellenbosch, 2010)
139 leaves printed single pages, preliminary pages i-xi and numbered pages 1-127. Includes bibliography and a list of figures and tables. Digitized at 600 dpi grayscale to pdf format (OCR),using a Bizhub 250 Konica Minolta Scanner.